Rancang Bangun Sepatu Roda Elektrik Berbasis Arduino: Indonesia - Damayanti, Eva; Suryanto, Ilham (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2022)
This journal discusses electric power-based vehicle technology or EV, where currently EV technology is developing rapidly demanding technological advances that are friendly to the environment, EV technology is combined with inline skating. This tool is specifically designed in a concise way so that it can be taken anywhere. The maximum speed of this tool is around 13 km/hour with a source of electricity using a rechargeable battery so there is no need to worry about fuel emissions. The type of battery used is LiPo with a capacity of 10400 mAh, with a charging time of around 6 hours 18 minutes. The footrest is also designed to be universal so that it can be used with shoes of various types and sizes. As well as gas and brake systems via a remote radio controller. This tool uses radio communication to communicate and send data to each other. The radio module used is the NRF24L01, which is a radio module that can receive and send data via 2.4 Ghz radio waves. Controlled using the Arduino Nano microprocessor. It is hoped that this tool can be an alternative short-distance transportation.